Safe tracheostomy in COVID-19 patients: a case series - Meghpara, Melissa K.; Devanabanda, Bhavana; Jimenez, Mercy; Louis, Martine A.; Mandava, Neil (International Surgery Journal, 2020)
The coronavirus (COVID-19) pandemic has led to a critical need in treating severe respiratory disease while providing adequate protection to healthcare workers. Critically ill COVID-19 patients have required prolonged intubation and mechanical ventilation, not limited to those with multiple comorbidities or the elderly. At the height of the pandemic in New York City; our institution intubated 192 COVID-19 patients. Many institutions have avoided performing tracheostomy in this population due to high risk of virus aerosolization. This study is a retrospective, IRB approved, single center case series of 14 consecutive tracheostomies in COVID-19 patients at a community hospital in Flushing, New York City. Data from 1 March to 31 May 2020 was collected from electronic medical records. All COVID-19 positive patients undergoing tracheostomy were included; patients undergoing tracheostomy that were not COVID-19 positive were excluded. Fourteen patients underwent tracheostomy during the study period. Average age was 62 and 64.3% were male (n=9). Hispanic males represented 50% of patients undergoing tracheostomy and 71.4% were from home. Average days from initial intubation to tracheostomy was 20.6, ranging from 12 to 43 days. With the exception of two patients, all underwent a single intubation. No involved operating room staff became ill during or after these procedures. Tracheostomy may be safely performed in COVID-19 patients while minimizing risk to staff; however, patient outcomes may not be significantly altered. Further research is needed to determine the optimal timing and overall benefit of tracheostomy in this population.